2019
DOI: 10.1186/s12913-019-4790-x
|View full text |Cite
|
Sign up to set email alerts
|

Why does the NHS struggle to adopt eHealth innovations? A review of macro, meso and micro factors

Abstract: BackgroundHaving a tax-funded and supposedly ‘National’ Health Service (NHS), one might assume that the UK is well-positioned to roll out eHealth innovations at scale. Yet, despite a strong policy push, the English NHS has been limited in the extent to which it has exploited the potential of eHealth.Main bodyThis paper considers a range of macro, meso and micro factors influencing eHealth innovation in the English NHS.ConclusionsWhile barriers to eHealth innovation exist at all scales, the fragmentation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 32 publications
1
71
0
Order By: Relevance
“…[9][10][11] While the NHS has published its 'Long Term Plan' on putting focus on digital transformation, it has been found that the fragmentation of NHS services is proving a barrier to change. 12 We have combined a phone clinic approach with the aid of the PKG as a surrogate for the clinical examination part of the clinical consultation. To our knowledge, this is the first pilot of a VC for patients with PD in the NHS.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] While the NHS has published its 'Long Term Plan' on putting focus on digital transformation, it has been found that the fragmentation of NHS services is proving a barrier to change. 12 We have combined a phone clinic approach with the aid of the PKG as a surrogate for the clinical examination part of the clinical consultation. To our knowledge, this is the first pilot of a VC for patients with PD in the NHS.…”
Section: Open Accessmentioning
confidence: 99%
“… 9–11 While the NHS has published its ‘Long Term Plan’ on putting focus on digital transformation, it has been found that the fragmentation of NHS services is proving a barrier to change. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not surprising that many health authorities, including the National Health Service (NHS) in the UK, used telemedicine during this pandemic, especially for outpatient follow-up [20,21]. Other uses of telemedicine can be seen in (including pre COVID-19) electronic prescribing and retrieving patient records [22]. One of the UK's Department of Health aims is that by 2023 there will be an established electronic system where patients' records can be accessed all over UK hospitals [23,24].…”
Section: Telemedicine and Online Teaching's Role In Dm Management Amimentioning
confidence: 99%
“…One of the UK's Department of Health aims is that by 2023 there will be an established electronic system where patients' records can be accessed all over UK hospitals [23,24]. Different IT systems and financial readiness in different hospitals can represent a huge obstacle in connecting different hospitals [22]. Furthermore, telemedicine can be labour intensive [22].…”
Section: Telemedicine and Online Teaching's Role In Dm Management Amimentioning
confidence: 99%
See 1 more Smart Citation